Formulasi dan Aktivitas Antibakteri Sediaan Sampo Ekstrak Getah Kemenyan (Styrax benzoin) - Susanti, Nora; Nainggolan, Chyntya Angelina Putri; Lubis, Syafrina Letare (Herbal Medicine Journal, 2025)
Dandruff is a common scalp disorder in Indonesia, often caused by an imbalance in bacterial and fungal populations such as Propionibacterium acnes and Pseudomonas aeruginosa. The use of synthetic active ingredients in shampoos may lead to irritation and microbial resistance, thus encouraging the development of natural alternatives. One promising natural ingredient is frankincense resin (Styrax benzoin), known for its bioactive compounds and antibacterial secondary metabolites. This study aimed to evaluate the antibacterial effectiveness of frankincense resin extract formulated into anti-dandruff shampoo. The extract was obtained through maceration using ethanol and formulated into shampoos with varying concentrations: 1% (F1), 3% (F2), 5% (F3), and 7% (F4). Antibacterial activity was tested using the disc diffusion method against Pseudomonas aeruginosa, Staphylococcus epidermidis, and Propionibacterium acnes. Shampoo evaluation included organoleptic properties, viscosity, and pH. The results showed that all formulas inhibited the growth of all test bacteria, with F4 exhibiting the largest inhibition zones against Pseudomonas aeruginosa (23.63 mm), Staphylococcus epidermidis (15.10 mm), and Propionibacterium acnes (30.83 mm). All formulations also met the quality parameters for topical preparations. These findings suggest that frankincense resin extract has strong potential as a natural antibacterial agent in anti-dandruff shampoo formulations with effective antimicrobial activity and good formulation quality.